2015
DOI: 10.1021/acsami.5b08126
|View full text |Cite
|
Sign up to set email alerts
|

Study of Osteoclast Adhesion to Cortical Bone Surfaces: A Correlative Microscopy Approach for Concomitant Imaging of Cellular Dynamics and Surface Modifications

Abstract: Bone remodeling relies on the coordinated functioning of osteoblasts, bone-forming cells, and osteoclasts, bone-resorbing cells. The effects of specific chemical and physical bone features on the osteoclast adhesive apparatus, the sealing zone ring, and their relation to resorption functionality are still not well-understood. We designed and implemented a correlative imaging method that enables monitoring of the same area of bone surface by time-lapse light microscopy, electron microscopy, and atomic force mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…It appears that a lifetime of only a few minutes is too short for further growth and stabilization, given that the time periods required for either ring expansion ( figure 5) or ring fusion (figure 6), exceed the intrinsic lifespan of small and dynamic SZs. As a possible trigger for the growth of some SZ rings (either on the smooth surface, or more prominently on the rough bone), we have previously observed the stabilization of small SZ rings by local bone protrusions with matching size [38]. Examination of the growing rings (more than 10 mm) indicated that unlike the small rings that either grow or uniformly collapse, the growing SZs display non-uniform dynamic behaviour, containing stable and unstable segments.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It appears that a lifetime of only a few minutes is too short for further growth and stabilization, given that the time periods required for either ring expansion ( figure 5) or ring fusion (figure 6), exceed the intrinsic lifespan of small and dynamic SZs. As a possible trigger for the growth of some SZ rings (either on the smooth surface, or more prominently on the rough bone), we have previously observed the stabilization of small SZ rings by local bone protrusions with matching size [38]. Examination of the growing rings (more than 10 mm) indicated that unlike the small rings that either grow or uniformly collapse, the growing SZs display non-uniform dynamic behaviour, containing stable and unstable segments.…”
Section: Discussionmentioning
confidence: 95%
“…Polished and unpolished bone slices were scanned using an atomic force microscope (NanoWizard R 3 Bioscience, JPK Instruments, Berlin, Germany), as described in [38]. Images were taken using contact mode in liquid (cell culture media, see §2.3).…”
Section: Atomic Force Microscopy Characterization and Roughness Analysismentioning
confidence: 99%
“…Osteoclasts were reported to be sensitive to topographical discontinuities that were in the tens of microns in culture matrices [21][22][23][24], but there has not yet been any clear evidence concerning the determinant factors for migration direction of such cells [24]. Possibly, odontoclast progression could be guided by micro/macro-morphological patterns on root surfaces, such as macroscopic surface curvature or surface asperities such as the micro-features resulting from PDL collagen fibre insertion and mineral crystal orientation [48], or the gradients of local mechanobiological stimulation.…”
Section: Size and Shape Characteristics Of Resorption Cratersmentioning
confidence: 99%
“…6 Researchers termed these structures as SZ rings, actin rings, or SZs. [7][8][9][10][11][12][13][14][15] The SZ defines the resorption area of the bone, consisting of a dynamic actin-rich ring-like structure which we have designated as a sealing ring since 2007. 1,2,[16][17][18][19][20] Our recent work has shown an important role for plastins in osteoclast biology, and the formation of actin-rich SZ structures.…”
Section: Introductionmentioning
confidence: 99%